proNGF Measurement in Cerebrospinal Fluid Samples of a Large Cohort of Living Patients With Alzheimer's Disease by a New Automated Immunoassay - Malerba, Francesca; Arisi, Ivan; Florio, Rita; Zecca, Chiara; Dell'Abate, Maria Teresa; Bruni Ercole, Bruno; Camerini, Serena; Casella, Marialuisa; Logroscino, Giancarlo; Cattaneo, Antonino (Frontiers in Aging Neuroscience, 2021)
The discovery of new biomarkers for Alzheimer’s disease (AD) is essential for an accurate diagnosis, to conceive new strategies of treatments, and for monitoring the efficacy of potential disease-modifying therapies in clinical trials. ProNGF levels in cerebrospinal fluid (CSF) represent a promising diagnostic biomarker for AD, but its validation was hampered by the absence of a reliable immunoassay. In the literature proNGF is currently measured in post mortem brain tissue by semiquantitative immunoblot. Here we describe the development and validation of a new method to measure proNGF in the CSF of living patients. This method, based on molecular size separation by capillary electrophoresis, is automated and shows a 40-fold increase in sensitivity with respect to the proNGF immunoblot, largely used in literature, and is robust, specific and scalable to high-throughput. We have measured proNGF in the cerebrospinal fluid of 84 living Alzheimer’s disease patients, in 13 controls, and 15 subjective memory complaints subjects (SMC). On comparing proNGF levels in the three groups, we found a very significant difference between proNGF levels in AD samples compared to both controls and SMC subjects, while no significant difference was shown between SMC and controls. Thanks to this new immunoassay, we are ready to explore the potentiality of proNGF as a new biomarker for Alzheimer’s Disease or subgroups thereof, as well as for other neurodegenerative diseases.